Expatriate performance in overseas assignments: the role of Big Five personality - Che Rose, Raduan; Sri Ramalu, Subramaniam; Uli, Jegak; Samy, Naresh Kumar (Canadian Center of Science and Education, 2010)
This paper investigates the affects of Big Five personality and its dimensions on expatriate job performance. Based on sample of 332 expatriates working in Malaysia, personality factor found to be a significant determinant of expatriate job performance in international assignments. Specifically, the results of this study reveal that expatriates in Malaysia with greater conscientiousness personality fared better in their task and contextual performance. Those with greater openness to experience found to perform better in their task, contextual and assignment-specific performance. The findings of this study contributes to the body of knowledge in the cross-cultural management field and have practical implication to expatriating firms especially in the area of selection and training of candidates for international assignments.